2020
DOI: 10.1186/s13229-020-0318-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics of Gabra4 knockout mice reveals common NMDAR pathways underlying autism, memory, and epilepsy

Abstract: Autism spectrum disorder (ASD) is a neuronal developmental disorder with impaired social interaction and communication, often with abnormal intelligence and comorbidity with epilepsy. Disturbances in synaptic transmission, including the GABAergic, glutamatergic, and serotonergic systems, are known to be involved in the pathogenesis of this disorder, yet we do not know if there is a common molecular mechanism. As mutations in the GABAergic receptor subunit gene GABRA4 are reported in patients with ASD, we elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…GRIN2B encodes the GluN2B subunit of NMDA receptors, ionotropic glutamate receptors that are essential for plasticity and brain development (Sanz-Clemente et al, 2013). Recently, GRIN2B has been identified as 1 of the 10 genes most likely to be key nodes that may control the larger network of autism risk genes (Fan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…GRIN2B encodes the GluN2B subunit of NMDA receptors, ionotropic glutamate receptors that are essential for plasticity and brain development (Sanz-Clemente et al, 2013). Recently, GRIN2B has been identified as 1 of the 10 genes most likely to be key nodes that may control the larger network of autism risk genes (Fan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is undoubtfully a fast and effective method to develop novel therapeutic targets by exploring shared molecular mechanisms of epilepsy and comorbid conditions [7]. There have been several studies show the shared molecular mechanisms of epilepsy and neuropsychiatric comorbidities, such as GABRA4, FZD7, Dlg4, and Vamp2 [10][11][12]. However, the association of epilepsy and digestive comorbidities are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [62], Kowalczyk et al [63] and Sun et al [64] revealed that the expression of ADCYAP1, NPAS4, NPSR1, HTR2C, GABRB2, ALOX12B, ADRB3, EGR3, HSPA1A and IL3RA are associated with progression of schizophrenia, but these genes might be novel target for AD. GABRA6 [65], GABRA1 [66], GABRG2 [67], SLC4A10 [68], HCN1 [69], GABRA4 [70], KCNC2 [71], SCN2A [72], SYN2 [73], FGF12 [74], SCN8A [75], OLFM3 [76], PLCB1 [77], KCNQ5 [78], TUBB2A [79], SIK1 [80], ABCC2 [81], SLC6A12 [82] and COL6A2 [83] have been reported to be closely related to the occurrence and development of epilepsy, but these genes might be novel target for AD. Previous investigation demonstrates that RGS4 [84] [92], NRN1 [93], SYT1 [94], GRIN2B [95], AVP (arginine vasopressin) [96], VSNL1 [97], HTR2A [98], PAK3 [99] [108], IGF1 [109], PLK2 [110], CBLN4 [111], CAP2 [112], SV2B [113], CAMK4 [114], INA (internexin neuronal intermediate filament protein alpha) [115] KIF5A [179] are associated with amyotrophic lateral sclerosis, but these genes might be novel target for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuzaki et al [55], Shepard et al [56], Lennertz et al [57], Klemettilä et al [58], Ullah et al [59], Kim et al [60], Sasayama et al [61], Li et al [62], Kowalczyk et al [63] and Sun et al [64] revealed that the expression of ADCYAP1, NPAS4, NPSR1, HTR2C, GABRB2, ALOX12B, ADRB3, EGR3, HSPA1A and IL3RA are associated with progression of schizophrenia, but these genes might be novel target for AD. GABRA6 [65], GABRA1 [66], GABRG2 [67], SLC4A10 [68], HCN1 [69], GABRA4 [70], KCNC2 [71], SCN2A [72], SYN2 [73], FGF12 [74], SCN8A [75], OLFM3 [76], PLCB1 [77], KCNQ5 [78], TUBB2A [79], SIK1 [80], ABCC2 [81], SLC6A12 [82] and COL6A2 [83] have been reported to be closely related to the occurrence and development of epilepsy, but these genes might be novel target for AD. Previous investigation demonstrates that RGS4 [84], CXCL11 [85], EGR1 [86], CALB1 [87], BDNF (brain derived neurotrophic factor) [88], TERT (telomerase reverse transcriptase) [89], NEFL (neurofilament light) [90], SNAP25 [91], RPH3A [92], NRN1 [93], SYT1 [94], GRIN2B [95], AVP (arginine vasopressin) [96], VSNL1 [97], HTR2A [98], PAK3 [99], STXBP5L [100], HCRTR2 [101], SYP (synaptophysin) [102], SYT10 [103], PRKCE (protein kinase C epsilon) [104], NRG1 [105], KISS1 [106], NRXN3 [107], RAB3A [108], IGF1 [109], PLK2 [110], CBLN4 [111], CAP2 [112], SV2B [113], CAMK4 [114], INA (internexin neuronal intermediate filament protein alpha) [115], GAP43 [116], TTR (transthyretin) [117], CXCR2 [118], IL1R2 [119], CXCR4 [120], CCR2 [121], MYOCD (myocardin) [122], S100A12 […”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation